Coastal urbanisation affects microbial communities on a dominant marine holobiont - Marzinelli, Ezequiel M. (NPJ Biofilms Microbiomes, 2018)
Host-associated microbial communities play a fundamental role in the life of eukaryotic hosts. It is increasingly argued that hosts and their microbiota must be studied together as 'holobionts' to better understand the effects of environmental stressors on host functioning. Disruptions of host–microbiota interactions by environmental stressors can negatively affect host performance and survival. Substantial ecological impacts are likely when the affected hosts are habitat-forming species (e.g., trees, kelps) that underpin local biodiversity. In marine systems, coastal urbanisation via the addition of artificial structures is a major source of stress to habitat formers, but its effect on their associated microbial communities is unknown. We characterised kelp-associated microbial communities in two of the most common and abundant artificial structures in Sydney Harbour—pier-pilings and seawalls—and in neighbouring natural rocky reefs. The kelp Ecklonia radiata is the dominant habitat-forming species along 8000 km of the temperate Australian coast. Kelp-associated microbial communities on pilings differed significantly from those on seawalls and natural rocky reefs, possibly due to differences in abiotic (e.g., shade) and biotic (e.g., grazing) factors between habitats. Many bacteria that were more abundant on kelp on pilings belonged to taxa often associated with macroalgal diseases, including tissue bleaching in Ecklonia. There were, however, no differences in kelp photosynthetic capacity between habitats. The observed differences in microbial communities may have negative effects on the host by promoting fouling by macroorganisms or by causing and spreading disease over time. This study demonstrates that urbanisation can alter the microbiota of key habitat-forming species with potential ecological consequences.